Public Market Energy Intensity and a Design of an Energy Efficient, Effective, Healthy and Vibrant Public Market Infrastructure - Manegdeg, Ferdinand G.; Espina, Mary Ann A.; Dalisay, Jon Dewitt E.; Pascual, Azero P. (MUHON: A Journal of Architecture, Landscape Architecture, and the Designed Environment; Issue Number 6, 2019)
Typical public markets in the Philippines are untidy, musty, and energy inefficient. This paper addresses the evaluation framework for energy intensity and general redesign of Philippine public markets considering low energy intensity, effective, healthy and vibrant conditions, and pleasing aesthetics as primary design considerations. Ten public markets were audited and evaluated. The average embodied energy is 4.7 PJ/m 2 and average monthly operation energy intensity is 19.2 MJ/m 2 . Optimizing the existing designs resulted to a 10.6 percent lower embodied energy and 64 percent lower operation energy intensity than the average of the study samples. However, considering the better criteria, an actual design has an embodied energy 10 percent more as expected but 55 percent lower operation energy intensity than the average of the study samples. It is recommended that the building code of public market include solar photovoltaic array and water heater, cold storage, bio-digester, solid waste disposal system, wastewater treatment, deodorizing and passive ventilation, and natural lighting.